Eduardo Augusto Kneese de Mello: his contribution to the collective housing in São Paulo - Regino, Aline Nassaralla; Perrone, Rafael Antonio Cunha (Risco - Journal of Architecture and Urbanism, 2009)
This article is about the work of Eduardo Kneese de Mello as an architect. It shows the professional as an active and distinguished figure in the dissemination and assertion of the Brazilian Modern Architecture, more precisely in São Paulo, during the 40's. It also shows his contribution to the Brazilian Architecture mainly through the quality of his work, his texts and his commitment to the broadening of passing on the culture of Architecture and Urbanism, added to the defense and legal consolidation of the professional qualifications of Architects. His work reveals, through the assessment of eight projects, its involvement, quite pioneer, to the collective housing projects in São Paulo.